Students' Perception of Hero Role Models National to Enhance National Spirit - Chaerulsyah, Edwin Mirza (Universitas Negeri Semarang, 2018)
Based on the research background, the problem issues to be studied are multifaceted and delve into various aspects of historical education and its impact on students (1) The study seeks to understand how history teachers at SMA Negeri 4 Tegal instill the values of exemplary national heroes in their teaching practices. This involves examining the methods and approaches used by these educators to highlight the qualities and contributions of national heroes, thereby fostering a strong sense of national spirit and pride among students (2) The research aims to explore the content and delivery of history lessons related to the national movement, the proclamation of independence, and the subsequent struggle for independence as taught in Classes X, XI, and XII at SMA N 4 Tegal. This part of the study will assess how these significant historical events are presented to students and the educational strategies employed to engage them with this crucial part of their national heritage (3) The research intends to gauge the perceptions of students at SMA Negeri 4 Tegal regarding the exemplary national heroes. This includes understanding how students view these figures, the impact of their stories on the student’s sense of identity and national pride, and how these perceptions influence their overall educational experience in history classes. Through these three focal points, the study aims to provide a comprehensive understanding of the role of history education in shaping national consciousness among high school students in Tegal.